Lope in Manhattan: Hyperreality, Space, and Violence in Julián Mesri’s «Fuenteovejuna» - Christopher D. Gascón (Universitat Autònoma de Barcelona, 2018)
This analysis of Repertorio Español’s 2013 production of Lope de Vega’s Fuenteovejuna in New York City focuses on the elements of communication, space, and violence. In director Julián Mesri’s staging, modern media or technology at times replace the human messengers of the original text, which has the double effect of distancing the audience emotionally from the events reported while calling attention to the mediums themselves and their agendas. In this contemporary urban world of simulacra, space seems compressed and violence appears conceptual. Mesri presents Fuenteovejuna as a Baudrillardian hyperreality, in which representations eclipse “reality.” In doing so, however, he does not so much alter Lope’s original as highlight, with modern touches, a dynamic that pervades the original play, Lope’s corpus, and much of Spanish Golden Age drama. Mesri’s vision may appear strikingly contemporary, yet the mode of representation it foregrounds is classic Lope.